Quantum Efficiency Enhancement of Bialkali Photocathodes by an Atomically Thin Layer on Substrates. Issue 23 (2nd December 2019) - Yamaguchi, Hisato; Liu, Fangze; DeFazio, Jeffrey; Gaowei, Mengjia; Guo, Lei; Alexander, Anna; Yoon, Seong In; Hyun, Chohee; Critchley, Matthew; Sinsheimer, John; Pavlenko, Vitaly; Strom, Derek; et al.
Abstract : Quantum Efficiency Enhancement Phototube with accelerator technology relevant antimonide photocathodes (K2 CsSb) deposited on atomically thin two‐dimensional (2D) crystal layers such as graphene. Quantum efficiency enhancement occurs in a reflection mode, when a 2D crystal is placed in between the photocathodes and optically reflective substrates. More details can be found in article number 1900501 by Hisato Yamaguchi, and co‐workers.